2000
DOI: 10.1097/00000542-200007000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cardiovascular Response to Airway Stimulation at Different Sites and Blockade of the Responses by Lidocaine

Abstract: We found that CVRs to tactile stimulation differ in their magnitude at three different sites within the airways, and localized anesthesia with lidocaine can abolish these responses in humans. The inhibition of lidocaine could be mainly due to direct blockade of the mechanoreceptors of the airways and partly to its systemic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 0 publications
0
54
0
4
Order By: Relevance
“…There are no publications concerning this issue to date but the effect of intravenous or topical lidocaine on preventing other adverse effects of airway interventions with the use of various instruments has been studied. These unwanted effects included haemodynamic disturbances [18,26,27], intraocular [28] or intracranial hypertension, postoperative airway symptoms [29] and bronchospasm in patients with bronchial asthma [30]. Ugur et al analysed the influence of lidocaine administration upon dispersion of the corrected QT interval (QTcd) and heart rate variability (HRV) occurring in patients in whom induction of anaesthesia was performed using sevoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…There are no publications concerning this issue to date but the effect of intravenous or topical lidocaine on preventing other adverse effects of airway interventions with the use of various instruments has been studied. These unwanted effects included haemodynamic disturbances [18,26,27], intraocular [28] or intracranial hypertension, postoperative airway symptoms [29] and bronchospasm in patients with bronchial asthma [30]. Ugur et al analysed the influence of lidocaine administration upon dispersion of the corrected QT interval (QTcd) and heart rate variability (HRV) occurring in patients in whom induction of anaesthesia was performed using sevoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate variability analysis has also been used to assess the autonomic effects of pharmacological agents, including beta-blockers, calcium blockers, antiarrhythmics, psychotrophic agents, and cardiac glycosides. 15,16) Owing to the fact that The different results obtained in studies using simple parameters are difficult to compare because of variations in the route of lidocaine administration, 7,19) speed of injection, dose, interval between administration and TI, 6,20) duration of TI, patient population, premedication, 21) additional use of opioids, 6) method of data collection, and statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the optimal timing for IV injection of lidocaine to minimize the haemodynamics upheaval induced by TI was 1-5 minutes 7,20,32) before TI. In addition, the study by Hamaga, et al, supported reasonable evidence that blood levels of subjects administered lidocaine decreased 5 minutes after injection.…”
Section: )mentioning
confidence: 99%
“…These results can be explained by the intense sympathetic stimulation during the end ES maneuver which was probably blocked by sedation and analgesia, not only by lidocaine although some studies have concluded that lidocaine does not attenuate cardiovascular response [14,15,29,35,36]. Nevertheless, Hamaya et al reported that the sympathetic responses mediated by the tactile stimulation of the larynx, tracheal carina and bronchi were completely blocked by ETL and partially blocked by IVL [14].…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine-injected IV blunts the cough reflex in awake and anesthetized patients and evidence demonstrates that lidocaine sprayed down the ETT attenuates the airway-circulatory reflexes during emergency and extubation after general anesthesia [13][14][15]. These facts prompted us to reappraise the issue of endotracheal lidocaine instillation for blunting ES induced cerebral hemodynamic changes in patients undergoing intensive care after severe head trauma.…”
Section: Introductionmentioning
confidence: 99%